Temperature variation and damage characteristic of impacted CFRP laminate using infrared thermography: Experimental investigation. (July 2018) - Li, Yin; Zhang, Rui-min; Li, Lei; Bao, Pan-pan; Zhang, Wei; Yang, Zheng-wei; Tian, Gan; Ming, An-bo
Highlights: Temperature evolution of impacted CFRP laminated is studied. Δ T max is defined to study temperature variation during fatigue. A method to determine COPs is proposed to facilitate the division of three stages. Damages characteristic of the impacted CFRP during fatigue is studied. Abstract: Infrared thermography is viewed as a promising method to investigate fatigue behavior and the objects studied in the available work are mainly focused on the metals and glass fiber reinforced plastic (GRFP), while the carbon fiber reinforced plastic (CFRP), especially the CFRP with initial impact damage, are rarely involved yet. In this work, experimental investigation on temperature variation and on damage characteristic of impacted CFRP laminate is conducted. Several specimens are begun with impact test and compression static test, followed by compression-compression fatigue test. Then, real-time maximum surface temperature difference, ΔTmax, is defined for investigating the temperature variation during fatigue and the obtained result shows that the evolution of Δ T max shows three stages in a " rapidly - slowly - rapidly " manner. On this basis, a method to determine the cut-off point is proposed to facilitate the division of the three stages, by which the three stages occupy less than 5%, more than 85% and less than 10% of total fatigue life respectively. Finally, the damage characteristic during fatigue is investigated. the obtained results show that the main damage characteristic changes in a " matrix crack-delamination-fiber rupture " manner as ΔT max proceeds.